The definition of model characteristics of motor activity in soccer referees - Абдула [Anatoliy Abdula] Анатолій Борисович (Slobozhanskyi Herald of Science and Sport, 2013)
A pedagogical observation and comparative analysis of motor activity FIFA international referees and referees highest, first, second league championship and the championship of Ukraine. Analyzed 120 games with referees with different qualifications. The most significant gap arbitrators Major League Ukraine Cup referees from the best found in terms of speed (jerks), coordination skills (running back, step ladders) and speed endurance (acceleration). In referees premier league referees regarding major league performance motor activity in lower accelerations and running backward and step ladders.